Legal Study Of Violence And Exploitation Against Child Trafficking From A Human Rights Perspective - Amarullah Siregar; Risdalina Risdalina; Maya Jannah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study was conducted to determine the factors causing violence and exploitation of child trafficking in the Rokan Hilir jurisdiction and legal protection efforts in overcoming violence and exploitation of child trafficking. This type of research is empirical legal research, in the form of problem analysis carried out by combining legal materials, both primary ones obtained in the field and secondary data. The problem approaches used include the legislative approach, conceptual approach and case studies. The legislative approach is by examining the legislation related to the legal issues studied, namely the crime of human trafficking. Data or information sources include primary data and secondary data. Primary data is data obtained in raw form and then analyzed further, originating from the community directly or law enforcement officers related to this research. While secondary data is data obtained through literature studies by studying literature, scientific writings, laws and regulations, and documents obtained by agencies related to the research object and the problems raised. Discussion Results: 1. Factors causing violence and exploitation of child trafficking in the Rokan Hilir jurisdiction include: economic factors, educational factors, environmental factors, law enforcement factors. 2. 1. Legal efforts to protect children who are victims of trafficking crimes are divided into 3 stages, namely protection at the time of the crime, the trial stage of the perpetrator of the crime and the stage after the court decision. Legal efforts to protect children who are victims of trafficking crimes are regulated in Law Number 21 of 2007 concerning the Eradication of Criminal Acts of Human Trafficking and Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. 2. Factors underlying the occurrence of child trafficking are economic factors, educational factors, environmental factors, law enforcement factors.